The role of UNESCO library programmes in the formation of national, regionai and international library policy - Macevičiūtė, Elena (Knygotyra, 1986)
The programmes of UNESCO concerning the development of libraries are among the factors that stimulate the attention of the governments and of the society of different countries to library work. The author reveals the main concepts of these programmes that deal with the attitude of governments, international organizations and other official agencies towards the problems of libraries concerning the development of science, culture and education.The article covers the period from 1967 — the first attempts to evaluate the possibilities of creating the international programmes in information and library work (UNISIST). The author shows the main features of UNISIST, NATIS, UBC, UAP and other programmes, their development and interpretations of their main concepts, their interconnection and impact on the development of library nets and systems on national and regional levels, on the changes taking place in international library organizations in connection with these programmes.It is difficult to evaluate the results of international activities. However, the fact that most countries of the world take part in the realization of UNESCO international library programmes, the development of national information systems according to the principles of NATIS and international information activities according to UNISIST speaks in favour of UNESCO influence in the development of library work in the world.
Keywords: -